A comparison of neuromuscular fatigue levels in collegiate baseball catchers and position players over a competitive season - Cardwell, Kathryn (My University, 2017)
PURPOSE: The purpose of this study was to investigate the development of neuromuscular fatigue of collegiate baseball players throughout the course of a competitive season. A secondary purpose was to determine if a difference of accumulated fatigue exists between baseball catchers, infielders and outfielders. METHODS: Thirty-Three Division II and III baseball players performed non-weighted countermovement and squat jumps on a force plate over 3 different testing sessions throughout a competitive season. Flight time: Contraction time (FT:CT) ratio and Eccentric Utilization Ratio (EUR) values were calculated using the variables derived from the force plate. Subjects also completed a Training Distress Scale survey at each of the testing sessions to assess subjective stress levels. RESULTS: A significant increase in FT:CT in baseball players over the season was detected between pre- and postseason (p=.001) and mid- and postseason (p=.005). No significant difference was detected using EUR over the course of the season (p=.853-1.00) or between positions (p=1.00). There was a significant increase in TDS scores between pre- and midseason (p=.054). CONCLUSION: Results indicated there was no evidence of neuromuscular fatigue development in collegiate baseball players throughout the course of the season.
Keywords: Baseball; Fatigue; College athletes